Adding Value to the UPM Experience - The Star, (2012)
With the tens of thousands that graduate from Malaysian universities each year - both public and private - one is tempted to ask if all graduates are the same,and if they aren't what is so different between a graduate from one university compared to another from some other university. Of course, every institution of higher learning, both public and private, boasts of its unique strengths, couched in terms like "rounded", "knowledgeable", "dedicated" "committed" and a host of other impressive adjectives.